PsycEXTRA Dataset 2006
DOI: 10.1037/e527352012-216
|View full text |Cite
|
Sign up to set email alerts
|

Getting a grip on numbers: Numerical magnitude priming in object grasping

Abstract: To investigate the functional connection between numerical cognition and action planning, the authors required participants to perform different grasping responses depending on the parity status of Arabic digits. The results show that precision grip actions were initiated faster in response to small numbers, whereas power grips were initiated faster in response to large numbers. Moreover, analyses of the grasping kinematics reveal an enlarged maximum grip aperture in the presence of large numbers. Reaction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Also, the finding of an enlarged MGA indicates an interaction between object perception and action planning. The effect on the grasping kinematics, moreover, parallels research demonstrating effects of size-related semantic information on grasping actions (Gentilucci, Benuzzi, Bertolani, Daprati, & Gangitano, 2000;Glover et al, 2004;Lindemann et al, 2007). Glover et al (2004) have shown that the modulation of the grip aperture by magnitude information reflects interference at the level of action planning.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Also, the finding of an enlarged MGA indicates an interaction between object perception and action planning. The effect on the grasping kinematics, moreover, parallels research demonstrating effects of size-related semantic information on grasping actions (Gentilucci, Benuzzi, Bertolani, Daprati, & Gangitano, 2000;Glover et al, 2004;Lindemann et al, 2007). Glover et al (2004) have shown that the modulation of the grip aperture by magnitude information reflects interference at the level of action planning.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, we observed that the MGA was larger while viewing a large object than while viewing a small object. The object size effect in the grasping kinematics demonstrates an impact of task-irrelevant magnitude information on motor behavior, as has previously been reported for word-reading and numberprocessing tasks Lindemann et al, 2007), and shows that similar effects also emerge during processing of visual 2 A cherry tomato, a tangerine, a carving fork, and a nail were used as sample objects for the training trials. information.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, bodily states can interplay with action initiation in number tasks. For example, Lindemann, Abolafia, Girardi, and Bekkering (2007) demonstrated that participants' hand grip openings were initiated faster and resulted in wider grip openings when responding to large numbers, compared to smaller grip openings for small numbers. Addi- Figure 1 .…”
Section: Embodied Numerical Cognitionmentioning
confidence: 99%
“…Besides number and space interactions, several studies showed that non-spatial kinematic parameters are systematically associated with number. For instance, grip aperture increases when large compared to small numbers are presented prior to the grasping movement (Andres, Davare, Pesenti, Olivier, & Seron, 2004;Andres, Seron, & Olivier, 2007;Chiou, Wu, Tzeng, Hung, & Chang, 2012;Lindemann, Abolafia, Girardi, & Bekkering, 2007). Other studies showed that small numbers are judged faster than large numbers when the response requires closing the index and thumb (precision grip) as for grasping a small object, whereas large numbers are judged faster than small numbers when the response requires opposing the fingers and the palm (whole-hand grip) as for grasping a large object (Chiou, Chang, Tzeng, & Wu, 2009;Moretto & di Pellegrino, 2008).…”
Section: Introductionmentioning
confidence: 99%